Creaky Acres - Brill, Calista; Magruder, Nilah (Kokila, 2025)
Ten-year-old African American Nora learns to love her new home in rural Greenville when she starts an eventing team with the horseback riders at Creaky Acres.
Keywords: Horses; Friends; Farm animals; Graphic novel